Ornement et Kunstwollen - Massimo Carboni (Images Re-Vues)
The concept of Kunstwollen, elaborated by the Austrian art historian Aloïs Riegl in his 1901 book, Late Roman art industry, has been very influent in XXth art theory. This article is therefore an innovative philosophical re-elaboration of this concept that relates it to ornament. According to Riegl and his contemporaries, adornment is often taken as the clearest expression of the Kunstwollen of a culture. This ornemental interpretation of Riegl's concept even authorizes to link it to a school of thought going from Bergson to Deleuze, and including Focillon's Life of forms, where ornament is no longer a simple add but is the expression of a vital force. Adornment is indeed a determining artistic element, to be related to the emergence of Abstract Art and Modernity.